Anticipated impacts in habitat of diagnostic species of potential natural vegetations due to climate change at the ecotone between temperate and boreal forests - Aurélie Chalumeau; Yves Bergeron; Mathieu Bouchard; Pierre Grondin; Marie-Claude Lambert; Catherine Périé (Climate Change Ecology)
Potential natural vegetations are crucial for forest research, management, and monitoring, especially considering their evolution amidst climate change. In Quebec (Canada), these vegetations were defined in the 2000s but haven't been updated since then. Originally, stability in their composition and dynamics relied on unchanged climate, soil characteristics, and disturbance regimes. However, in the southwestern part of Quebec forests, we have enhanced the description of potential natural vegetations using diagnostic species, based on their indicator values and relative abundance. This improvement prompts a reevaluation of these vegetations, particularly at the transition between temperate and boreal forests, considering climate change. Our study, using tree habitat suitability models, reveals that even under a moderately warming scenario (2041–2070 RCP 4.5 W m−2), diagnostic coniferous and boreal hardwood species face habitat suitability declines but the current classification remains adequate. However, a more severe warming scenario (2071–2100 RCP 8.5 W m−2) results in significant habitat unsuitability for these diagnostic species, questioning the relevance of the current classification at the ecotone. Given the crucial tool of potential natural vegetations in forest management, updating their classification becomes imperative to guide forestry practices' adaptation to climate change.